1995
DOI: 10.1002/1097-0142(19950801)76:3<343::aid-cncr2820760302>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Progress in reducing nausea and emesis. Comparisons of ondansetron (zofran), granisetron (kytril), and tropisetron (navoban)

Abstract: Background. Nausea and vomiting are the most distressing side effects associated with the administration of chemotherapy for neoplastic diseases. Nausea, in particular, often had been ignored in studies of chemotherapy side effects. Recently, progress has been made in the control of chemotherapy‐induced nausea and vomiting, due, in part, to a better understanding of the physiologic mechanisms involved. Methods. This paper reviews recent advances in the control of emesis, focusing on pharmacologic treatments. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
50
0
2

Year Published

1999
1999
2009
2009

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 92 publications
(52 citation statements)
references
References 83 publications
0
50
0
2
Order By: Relevance
“…Nausea is accompanied by changes in autonomic nervous system activity, particularly parasympathetic activity, diminished gastric tone, reduced peristalsis and retrograde peristalsis, and retrograde duodenal peristalsis." Vomiting is the "forceful emptying of the gastric contents through the sustained action of abdominal muscles and the opening of the gastric cardia [1] ." Nausea and vomiting occur under a variety of conditions, Paul Enck, Dr, Professor, Series Editor www.wjgnet.com such as in cancer chemotherapy, after vestibulary stimulation (motion sickness), or during pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…Nausea is accompanied by changes in autonomic nervous system activity, particularly parasympathetic activity, diminished gastric tone, reduced peristalsis and retrograde peristalsis, and retrograde duodenal peristalsis." Vomiting is the "forceful emptying of the gastric contents through the sustained action of abdominal muscles and the opening of the gastric cardia [1] ." Nausea and vomiting occur under a variety of conditions, Paul Enck, Dr, Professor, Series Editor www.wjgnet.com such as in cancer chemotherapy, after vestibulary stimulation (motion sickness), or during pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…For example, data from University of Rochester Cancer Center Community Clinical Oncology Program Research Base study showed that 77% of patients with highly emetogenic therapies experienced delayed nausea and 20-30% of patients suffered anticipatory nausea or vomiting. 41,42 Therefore, it is necessary to develop new modalities to control postchemotherapy nausea and vomiting. In the 2009 ASCO annual meeting, the results of RCT testing the efficacy of ginger in alleviating the post-chemotherapy nausea were presented.…”
Section: Ginger For Chemotherapy-related Nauseamentioning
confidence: 99%
“…The discovery of the 5-HT 3 receptor antagonists has dramatically improved the treatment of emesis induced by anti-cancer therapy (Aapro, 1991;Morrow et al, 1995). Their major bene®cial eects were observed in the acute phase of chemotherapy-induced emesis in animal models (Bermudez et al, 1988;Higgins et al, 1989;Rudd & Naylor, 1996) and in humans (Morrow et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Their major bene®cial eects were observed in the acute phase of chemotherapy-induced emesis in animal models (Bermudez et al, 1988;Higgins et al, 1989;Rudd & Naylor, 1996) and in humans (Morrow et al, 1995). However, 5-HT 3 receptor antagonists such as ondansetron and granisetron failed to control the delayed nausea and vomiting associated with chemotherapy (De Mulder et al, 1990;Butcher, 1993).…”
Section: Introductionmentioning
confidence: 99%